THE IRRIGATION PROPERTIES OF THE DEBED RIVER WATER (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
In terms of industrial pollution of the RA the technogenic factor has got a decisive influence on the chemical composition of the water of the Debed River. As a result of the technogenic pollution, these waters have a very unique chemical composition that is different from river water, formed under the influence of natural factors. They are characterized by a high content of heavy metals and hence unsatisfactory irrigating properties. Irrigation, using such waters, leads to soil pollution by heavy metals.
Keywords: Debed River; technogenic factor; chemical composition of the water; content of heavy metals